Micron‐sized polystyrene particles by surfactant‐free emulsion polymerization in air: Synthesis and mechanism. Issue 19 (10th July 2013) - Telford, Andrew M.; Pham, Binh T. T.; Neto, Chiara; Hawkett, Brian S.
<x xml:space="preserve">Abstract</x> In this study, a novel, robust approach is presented to produce micrometer‐scale‐sized polystyrene particles with narrow size distribution in highly concentrated latexes. The approach could be easily employed by those not skilled in the art to produce large quantities of polymer particles for research applications. A recent hypothesis is corroborated for the mechanism of particle growth in surfactant‐free emulsion polymerization, based on heterocoagulation of precursor particles onto mature ones. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>